2015
DOI: 10.1155/2015/165078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical (In)activity on Platelet Function

Abstract: As platelet activation is closely related to the liberation of growth factors and inflammatory mediators, platelets play a central role in the development of CVD. Virtually all cardiovascular risk factors favor platelet hyperreactivity and, accordingly, also physical (in)activity affects platelet function. Within this paper, we will summarize and discuss the current knowledge on the impact of acute and habitual exercise on platelet function. Although there are apparent discrepancies regarding the reported effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 119 publications
3
65
3
Order By: Relevance
“…[33] Additionally, it has previously been shown that the effect of acute exercise on platelet function depends on the intensity of the exercise, with only strenuous exercise temporarily increasing platelet reactivity and moderate exercise being shown to suppress platelet reactivity. [34][35][36] Therefore, whereas the acute high intensity cycling exercise trial in our previous study likely would have resulted in an increase in platelet reactivity, the small muscle mass moderate level exercise undertaken in this study would most likely not. [34][35][36] In this study we show for the first time how the systemic effect of increased levels of noradrenaline alters clot microstructure formation and can promote abnormal clot formation.…”
Section: Discussionmentioning
confidence: 72%
“…[33] Additionally, it has previously been shown that the effect of acute exercise on platelet function depends on the intensity of the exercise, with only strenuous exercise temporarily increasing platelet reactivity and moderate exercise being shown to suppress platelet reactivity. [34][35][36] Therefore, whereas the acute high intensity cycling exercise trial in our previous study likely would have resulted in an increase in platelet reactivity, the small muscle mass moderate level exercise undertaken in this study would most likely not. [34][35][36] In this study we show for the first time how the systemic effect of increased levels of noradrenaline alters clot microstructure formation and can promote abnormal clot formation.…”
Section: Discussionmentioning
confidence: 72%
“…4,5). Rheological alterations are currently linked to morbidities such as: diabetes, hereditary disorders, sickle cell, myocardial infarction, paroxysmal nocturnal hemoglobinuria, sepsis, end stage renal disease, hypertension, strokes, endothelial function, vascular health, hemostasis in athletes and blood transfusions and cancer (Hung et al 1991;Pechan et al 1991;McHedlishvili and Maeda 2001;Ahmad and El-Sayed 2003;Meiselman 2003, 2010;Piagnerelli et al 2003;Babu and Singh 2004;Meiselman et al 2007;Forsyth et al 2012;Serroukh et al 2012;Beck et al 2014;Giovanna 2014;Hierso et al 2014;Buttari et al 2015;Heber and Volf 2015;Ertan et al 2017). Interestingly, we also observed many rheological alterations in our "healthy" pilot study participants (Figs.…”
Section: Introductionmentioning
confidence: 99%
“…Hematological parameters, including WBC, RBC, platelet count, hematocrit, MCV, MCH, MCHC, MPV, and hemoglobin, are affected by pathological and physiological conditions (Rodak, Frisma, & Keohane, ). In addition, exercise can induce the release of platelets from the spleen and increase the circulating platelet count (Heber & Volf, ). It is interesting that in the exercise group, hemoglobin, MCH, and MCHC decreased significantly.…”
Section: Discussionmentioning
confidence: 99%